The Influence of Work Incentives and Motivation on the Performance of Certified PNS Teachers at SMP Negeri 1 Sei Suka Batubara District - Jopinus Saragih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The results of this research show. (1) It can be seen that the adjusted R square value is 0.688 or 68.8%. This shows that the Incentive Variable (X1) and Work Motivation Variable (X2) can explain the Performance Variable (Y) of 68.8%, the remaining 31, 2% (100% - 68.8%) is explained by other variables outside this research model. (2) The results of the t test (Partial) show that tcount (3.969) > ttable (1.699), likewise with a significance value of 0,00< 0.05 then the hypothesis can be concludedfirst accepted, meaningThe Incentive Variable (X1) has a significant effect on the Performance Variable (Y).(3) The results of the t test (Partial) can be seen that the value of tcount (7,822) > ttable (1.699), and the significance value is 0.202 > 0.05, it can be concluded that the second hypothesis is rejected, meaningThe Work Motivation variable (X2) has a significant effecton the Performance Variable (Y). (4) Simultaneous test results (F) can be seen that the value of Fcount (34,461) > Ftable (3.25), and the significance value is 0,00< 0.05, it can be concluded that the third hypothesis is accepted, meaningIncentive Variable (X1), Work Motivation Variable (X2) have a significant effect together (simultaneously) on the Performance Variable (Y).